La expresión musical como herramienta para el desarrollo integral en la educación infantil - Sigcha Ante, Erika Maribel (2016)
In education system takes into account the music from a traditional point of view, it used as memory activity and not dynamics in order to apply in the kindergarten, and the most used strategies is the musical expression, being an important methodological tool within the education initial, Gardner and many authors mention that through the music it can develop skill, ability in order to reinforce different learning area, but there is always fun, and it helps to stimulate the four areas of child as are: motor, cognitive, socio-emotional and language area with a significant learning, in where the children increase their learning with environment resources, with a suitable environment for the integral development, through this research was observed that the multiple benefits that this provides and deficiencies resulting in its absence, therefore arose the need of strengthen in them teaching the importance of the expression Musical in the development Integral child with activities innovative raised from educators with new perspectives, following a research methodology , focused on solving the problems through a critical and systematic analysis, for which the respective data collection instruments applied, obtaining results favorable, as is proved that not is necessary the use of instruments music, because a child at this age has a relevant imagination learning through songs, stories, pictograms, tongue twisters, to the dance, to the paint and even can associate the song with experiences already lived in where that same song already was heard, being of great importance to use dynamically the music in our children, having an impact first social because is managed to join ties of fellowship between children, there was wide acceptance and interest both parents and the teachers from the institution, showing that a teacher should not lose its essence of being teacher, their love and vocation for what makes to the moment of instilling knowledge, but must rather always be self - educating with new innovative strategies that contribute to the development full, spiritual, social and cognitive infant generating bodies of knowledge that will provide a contribution to society and to the development of the same.